2004
DOI: 10.1016/j.orthres.2003.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Endochondral ossification in fracture callus during long bone repair: The localisation of ‘cavity‐lining cells’ within the cartilage

Abstract: Successful fracture healing typically involves the production of a cartilaginous callus, which is eventually remodelled into new bone. The blood vessels in the advancing front of endochondral ossification are likely to play an important role in the replacement of cartilage with bone within the callus. This was investigated by histology and immunohistochemistry techniques carried out on rabbit tibia1 osteotomy tissue. Cavities within the cartilage were identified by histology and in many cases, there appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Murine bone marrow transplantation studies have demonstrated that bone marrow populations enriched for HSCs, including the non-adherent bone marrow population [11; 43] and the bone marrow side population [10], give rise to osteoblasts in vivo . Cells positive for CD34 and osteocalcin (“osteoblastic cells”) were found to line the cavities of the cartilage in the fracture site of rabbit tibial osteotomy model [44]. Transplantation of human CD34 + cells into immunocompromised rats with fracture non-union resulted in significant enhancement of functional bone healing [45].…”
Section: Discussionmentioning
confidence: 99%
“…Murine bone marrow transplantation studies have demonstrated that bone marrow populations enriched for HSCs, including the non-adherent bone marrow population [11; 43] and the bone marrow side population [10], give rise to osteoblasts in vivo . Cells positive for CD34 and osteocalcin (“osteoblastic cells”) were found to line the cavities of the cartilage in the fracture site of rabbit tibial osteotomy model [44]. Transplantation of human CD34 + cells into immunocompromised rats with fracture non-union resulted in significant enhancement of functional bone healing [45].…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinases are also involved in TGFmediated induction of SMAD2/3 phosphorylation (Park et al, 2010), calling for the mutual influence of the substrata and/or microenvironments on the cells differentiative properties. In in vivo fracture healing experimental systems the cartilaginous callus is remodeled into new bone; the blood vessels in the advancing front of the endochondral ossification play a relevant role in the cartilage-to-bone conversion (Ford et al, 2004), while ischemia correlates with failure of skeletal repair (Lu et al, 2007). TGF is required for proper angiogenesis and vascular tree formation (Darland and D'Amore, 2001) and it may prime the cells to produce mediators for vascular invasion, as it happens for TGF b-1 direct targeting of the MCP-1 gene via SMAD3/4 in wound healing assays (Ma et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mobilized Sca1+Lin− cells were immunohistochemically proved to incorporate into the fracture site and differentiate into mature ECs. Recently, Ford demonstrated that CD34+ cells line the cavities of the cartilage in the fracture site in a rabbit tibial osteotomy model (Ford et al, 2004). In our previous study, transplanted human CD34+ cells were shown to differentiate into ECs at the fracture site of an immunodeficient rat fracture model (Matsumoto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%